Vegetal test-system investigation on cytotoxicity of water from urban streams located in the northeastern region of Maringá, Paraná State, Brazil - doi: 10.4025/actascibiolsci.v33i1.4924 - Elisângela Düsman; Juliana Sala de Faria; Fabiana Toledo; Camila Montoro Mazeti; Marcus Eduardo Kamide Gonçalves; Veronica Elisa Pimenta Vicentini (Acta Scientiarum. Biological Sciences, 2011)
The increase in consumption of water, the destruction of riparian forests and the pollution caused by humans, have severely degraded several water resources. Numerous stream crisscross the city of Maringá, Paraná state, Brazil and most of their sources are scattered through the urban region. Current analysis assesses the cytotoxic potential of water from the Corregozinho, Isalto, Morangueira and Ozório streams, located within the high-populated northeastern region of Maringá, inside the urban perimeter. Root meristematic cells of Allium cepa were used as test-system. The roots of onion were prepared by Feulgen’s reaction and stained with Schiff's reagent. Results showed that there were no statistically significant changes evaluated by the chi-square test on the rates of cell division in cells of Allium cepa roots treated with the water of the streams when compared to data from controls. However, further analyses should be undertaken at different times for a periodic assessment of conditions in the streams, coupled with an awareness of the population on the environment.